Laparoscopic hysterectomy for benign pathology does not yield more perioperative complications than abdominal or vaginal hysterectomies: Our experience in introducing laparoscopic hysterectomy - Akimasa Takahashi; Mao Uemura; Jun Kitazawa; Mari Nakata; Yoshihiko Hayashi (Wolters Kluwer Medknow Publications, 2020)
Objectives: Total laparoscopic hysterectomy (TLH) is increasing as a substitute for total abdominal hysterectomy (TAH) and total vaginal hysterectomy (TVH) with the growing prevalence of laparoscopic surgery. The aim of this study is to assess perioperative complications of the chosen hysterectomy techniques performed for benign indications when started performing TLH. This was retrospective cohort study. This study was conducted at Nagahama City Hospital. Materials and Methods: There were 176 patients who underwent hysterectomy for benign indications from 2013 to 2016. Perioperative and postoperative outcomes were compared for the three different hysterectomy approaches laparoscopic; abdominal; and vaginal. Data were analyzed using the t-test or Chi-square and Fisher's exact test. Results: TAH, TLH, and TVH were performed on 118 patients (67.0%), 32 (18.2%), and 26 (14.8%), respectively. Operation time was significantly longer for the TLH group than for the TAH and TVH groups. Blood loss was lower for the TVH and TLH groups than for the TAH group. Three days after surgery, C-reactive protein was lower in the TVH group than in the TAH group. The average uterus size in the TAH group was larger than in the TVH and TLH groups. Patients undergoing TLH experienced fewer perioperative complications than patients in the TAH and TVH groups; however, this difference was not statistically significant. Conclusion: TLH for benign pathology does not yield more perioperative complications than TAH or TVH. However, vaginal hysterectomy is the least invasive approach. The final choice for the route of hysterectomy depends on many factors, including body mass index, uterus size, and experience of the gynecologist.